Challenges Faced by Older Persons in Eastern and Southern Africa and Implications for Social Work Practice - Jotham Dhemba (Social Work & Society, 2024)
This article explores the challenges faced by older persons in Eastern and Southern Africa and their implications for social work practice. The phenomenal increase in the number of older persons in Eastern and Southern Africa, like elsewhere regionally and internationally, is occurring in a context where this demographic shift is yet to be matched with the resources, skills and government commitment to respond to their needs. As a result, older persons in Eastern and Southern Africa face a myriad of challenges including poverty, food insecurity, poor health and lack of or limited access to social services, abandonment and neglect, and abuse. Their plight is exacerbated by diminishing inter-generational support, due to the pervasiveness of poverty in these countries, and sociocultural processes such as modernisation, globalisation, migration and urbanisation. Nonetheless, although ageing cannot be prevented, some of its consequences can be mitigated or delayed to enable older persons to age successfully and with dignity. As such, vulnerability in old age requires new frameworks of support to ensure their well-being. In this regard, the Global Agenda for Social Work and Social Development 2012 commits social workers to promote social and economic justice and the dignity and sanctity of human life, older persons included.